Combined Effects of Allelopathic Polyphenols on Microcystis aeruginosa and Response of Different Chlorophyll Fluorescence Parameters - Huang, Suzhen; Zhu, Junying; Zhang, Lu; Peng, Xue; Zhang, Xinyi; Ge, Fangjie; Liu, Biyun; Wu, Zhenbin (Frontiers in Microbiology, 2020)
Polyphenols are allelochemicals secreted by aquatic plants that effectively control cyanobacteria blooms. In this study, sensitive response parameters (including CFPs) of Microcystis aeruginosa were explored under the stress of different polyphenols individually and their combination. The combined effects on M. aeruginosa were investigated based on the most sensitive parameter and cell densities. For pyrogallic acid (PA) and gallic acid (GA), the sensitivity order of parameters based on the EC50 values (from 0.73 to 3.40 mg L-1 for PA and from 1.05 to 2.68 mg L-1 for GA) and the results of the hierarchical cluster analysis showed that non-photochemical quenching parameters (NPQ, qN, qN(rel) and qCN) > photochemical quenching parameters (YII, qP, qP(rel) and qL) or others (Fv/Fm, F′v/F′m, qTQ and UQF(rel)) > cell densities. CFPs were not sensitive to ellagic acid (EA) and (+)-catechin (CA). The sensitivity order of parameters for M. aeruginosa with PA-GA mixture was similar to that under PA and GA stress. The quantitative (Toxicity Index, TI) and qualitative (Isobologram representation) methods were employed to evaluate the combined effects of PA, GA and CA on M. aeruginosa based on cell densities and NPQ. TI values based on the EC50cells suggested the additive effects of binary and multiple polyphenols, but synergistic and additive effects according to the EC50NPQ (varied from 0.16 to 1.94). In terms of NPQ of M. aeruginosa, the binary polyphenols exhibited synergistic effects when the proportion of high toxic polyphenols PA or GA was lower than 40%, and the three polyphenols showed a synergistic effect only at the ratio of 1:1:1. Similar results were also found by isobologram representation. The results showed that increasing the ratio of high toxic polyphenols would not enhance the allelopathic effects, and the property, proportion and concentrations of polyphenols played an important role in the combined effects. Compared with cell densities, NPQ was a more suitable parameter as evaluating indicators in the combined effects of polyphenols on M. aeruginosa. These results could provide a method to screen the allelochemicals of polyphenols inhibiting cyanobacteria and improve the inhibitory effects by different polyphenols combined modes.